Produciendo a Sahagún: El problema de la autoría en Sahagún, Pablo de San Buena Ventura, Antonio Valeriano, Alonso Vegerano, Martín Jacobita y otros, o Sahagún y los neo-tlacuilos (Revista de Crítica Literaria Latinoamericana, 2017)
Taking into consideration the extensive and sustained participation of Aztec post conquest tlacuilos in the various aspects of gathering, composition, preparation, alphabetic rendition and interpretation of the huge Nahuatl text gathered in the work of Sahagún, this study seeks to de-stabilize the notion on Sahagún as the author of the Códice Florentino and all the other texts known as his work. In doing so, this study also questions the received concept of Mestizaje as it implies consolidated individual or group’s consciousness despite the conflicting and often unresolved double voicing at the heart of historical Mestizaje.Rather than resolution of conflicts or contradictions in the post-conquest situation of Sahagun and the tlacuilos, this study brings to the fore the cultural and epistemological flux of the writing scenes in which the sui generis work comes into being.
Keywords: Sahagun; Neo-tlacuilos; Codice Florentino; Mestizaje; Autorship